Tinjauan Yuridis Penyelenggaraan Pemungutan Retribusi Pelayanan Parkir Di Tepi Jalan Umum - Muhammad Ishomudin (Lex Renaissance, 2019)
This study aims to analyze the implementation of the Bantul District Regulation No. 19 of 2015 on Road Traffic and Transportation Network (Bantul District Regulation) in regard to parking on the public roadside in Bantul. This research is motivated by the large number of public roadside used as vehicle parking lots by most people in Bantul District. The formulation of the problems is: how is the implementation of the Bantul District Regulation in providing parking on public roadside? what is the process for applying for a roadside parking permit?; what is the surveillance system for collecting roadside parking fees?; and what is the legal step of the Bantul Regency Government if the application of public roadside parking violates the provisions in the licensing?. This research uses a juridical-empirical method by collecting data through literature and field studies with qualitative-descriptive analysis. The results showed that Regional Regulation No. 09 of 2011 on Public Service Levies cannot be used as a basis for parking service providers. The Bantul District Government then issued a Bantul District Regulation that gave authority to the Department of Transportation. But in reality, many parking providers have postponed parking fee payments to the Department of Transportation.